MiR-4728-3p Functions as a Tumor Suppressor in Ulcerative Colitis-associated Colorectal Neoplasia Through Regulation of Focal Adhesion Signaling. Issue 8 (9th June 2017) - Pekow, Joel; Hutchison, Alan L.; Meckel, Katherine; Harrington, Kymberly; Deng, Zifeng; Talasila, Nitya; Rubin, David T.; Hanauer, Stephen B.; Hurst, Roger; Umanskiy, Konstantin; Fichera, Alessandro; Hart, John; et al.
Abstract : Background: As mechanisms of neoplasia in patients with ulcerative colitis (UC) remain poorly understood, we sought to identify pathways of carcinogenesis in this high-risk population. Methods: MicroRNA (miRNA) and mRNA expression was examined in nondysplastic rectosigmoid mucosa from UC patients with (n = 19) or without remote colon neoplasia (n = 23). We developed a method to identify miRNA-regulated pathways based on differentially expressed miRNAs and their putative mRNAs targets in the same samples. One key pathway identified in the analysis, miR-4728-3p regulation of focal adhesion signaling was further evaluated in vitro and through examination of expression in UC-cancers. Results: There were 101 significantly up-regulated and 98 down-regulated miRNAs (adjusted P < 0.05) in the rectal mucosa of UC patients harboring proximal neoplasia. Bioinformatic analysis identified miR-4728-3p as a regulator of 3 proteins involved in focal adhesion signaling, CAV1, THBS2, and COL1A2. Real-time PCR validated down-regulation of miR-4728-3p in nondysplastic tissue remote from UC-neoplasia and in UC-associated colon cancers. miR-4728-3p transfection into colon cancer cells down-regulated expression levels and decreased luciferase activities in cells expressing a wild type 3′ untranslated region compared with a mutant 3′ untranslated region for all 3 genes. Exogenous transfected miR-4728-3p also delayed wound healing and decreased formation of focal adhesion complexes. Conclusions: Patients with long-standing UC who harbor neoplasia can be identified based on miRNA and mRNA profiles in nondysplastic tissue. Using a method to analyze miRNA and mRNA expression from the same tissues, we identified that miR-4728-3p is likely an important tumor suppressor in UC-associated colon carcinogenesis.